Prison Regimes - Vega Santa Gadea, Fernando (1972)
The present work begins by mentioning that the study of prison law is still incipient and briefly develops the history of its formation and the establishment of prisons in North America; as well as its influence in Europe and Latin America. In this regard, the author addresses the practices employed in prison regimes for the treatment of prisoners and the transit of practices considered cruel and inhuman, involving physical punishment and/or isolation,  measures that consider the possible resocialization of the accused. Finally, the author closes the analysis by recognizing the importance of having new penological experiences that contemplate the readaptative treatment.